(3QSGdI aj OaY GdeVGQ GdcdjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s; (3CHhSgd , YjSi Hf jMji GdeSjMj GdLQLGfj,J (B401 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdTjN CHG GdMSjf CMeO Hf eMeO GdSgdi Cf CYed cJGHkG ai OaY GdeVGQ GdcdjI ddCHOGf GdEfSGfjI s
(3BNQgG (B:s
(3jfHZi Cf jLJgO ai MHS GdWHjYI Ke jJfGhd GdeZQjGJ eY UaQI GdHjV hGdCcGQY hdjcf gPG cGa ai ZQVfG hGddg CYde Je s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B35s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B757s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdWHs